1997
DOI: 10.1016/s0304-3959(97)03333-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic sensitivity to hot-plate nociception in DBA/2J and C57BL/6J inbred mouse strains: possible sex-specific mediation by δ2-opioid receptors

Abstract: The inbred mouse strains, DBA/2J (D2) and C57BL/6J (B6), display differential sensitivity to acute, thermal nociception as measured on the hot-plate (HP) assay. In an ongoing quantitative trait locus (QTL) mapping study designed to reveal genomic loci showing genetic linkage to HP sensitivity, a putative QTL on chromosome 4 (50-80 cM from the centromere) has been identified that appears to account for variability in this trait in male, but not female mice. An obvious candidate gene located in this same chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
4

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(46 citation statements)
references
References 66 publications
1
41
0
4
Order By: Relevance
“…In Lewis rats, sex differences in baseline tail-withdrawal latencies were not obtained, nor were there consistent differences in κ opioid sensitivity. Studies in mice have found a similar correlation between baseline nociceptive latencies and sensitivity to morphine-induced antinociception, with morphine being more potent in strains with longer baseline latencies (Mogil et al 1996(Mogil et al , 1997Elmer et al 1998).…”
Section: Discussionmentioning
confidence: 91%
“…In Lewis rats, sex differences in baseline tail-withdrawal latencies were not obtained, nor were there consistent differences in κ opioid sensitivity. Studies in mice have found a similar correlation between baseline nociceptive latencies and sensitivity to morphine-induced antinociception, with morphine being more potent in strains with longer baseline latencies (Mogil et al 1996(Mogil et al , 1997Elmer et al 1998).…”
Section: Discussionmentioning
confidence: 91%
“…Injury Type-Specific Ca 2؉ Channel ␣ 2 ␦-1 Subunit Regulation onist treatment in mice with acute, thermal nociception (Mogil et al, 1997). Even though it was not proven, it was less likely that altered pharmacokinetics of gabapentin accounted for the gabapentin insensitivity in VIN rats because the antiallodynic effects of gabapentin in other models, including the DB model, occurred quickly after intraperitoneal administration.…”
Section: Discussionmentioning
confidence: 99%
“…By using similar methodology to that described above, we recently mapped basal thermal nociceptive sensitivity by using the hot-plate test (94). The most promising of six putative linkages in BxD RI strains-the D4Mit71 region (50-70 cM) of mouse chromosome 4-was largely confirmed by using F 2 mice.…”
Section: Identification Of Pain-related Genesmentioning
confidence: 99%